O cuidado à autolesão não suicida na percepção de adolescentes, jovens e enfermeiras: revisão sistemática de estudos qualitativos - Lopes, Daniela Gonsalves (Universidade Federal de São Carlos, 2021)
Objective: Adolescence and youth are processes of human development that must be understood as singular and contextual moments. Due to the characteristics of these periods, this population may be more exposed to violence, including self-inflicted violence. Non-suicidal self-injury can be defined as a deliberate injury that results in the destruction or alteration of the person's body tissue. Regarding the care of these adolescents and young people, it is a fact that Nursing occupies a privileged place in health teams and services, being essential for the systematization of a sensitive, coherent and unique care plan for self-injury. However, the production of scientific knowledge about nursing care to this phenomenon in adolescence and youth has gaps. Considering the above, the aim of this study was to synthesize the knowledge produced by qualitative studies on barriers and facilitators for nursing care at NSSI on the perception of adolescents, young people and nurses. It was a systematic literature review, using meta-aggregation to synthesize the studies, according to the Joanna Briggs Institute. The search was conducted at the BVS, PUBMED; PUBMED PMC; CINAHL; Web of Science; PsycInfo; EBSCOhost; Scopus Preview and Embase, completed in January 2021. In addition, an evaluation of the methodological quality of the studies was carried out. Of the 1540 studies found, eleven studies were included after assessing methodological quality. After the meta-aggregation, two synthesized findings emerged and were titled “Humanized Care” and “Nurses and Services Preparation”. It became evident that this care to be efficient needs to be carried out in a humanized way, with the construction of trust. It was also identified that when carried out in non-specialized mental health units, it needs to be developed and improved. Conclusion: Nursing care for non-suicidal self-injury in adolescence or youth occurs inconsistently and unsatisfactorily for the needs of this population, based on specific actions and focused on a biomedical strategy, not providing the creation of the bond and, thus, not guaranteeing continuity of care. New studies are needed in countries with greater social vulnerability and in other social and cultural contexts, in addition to conceptual definitions of NSSI and suicidal behaviors for better performance of Nursing and health.
Non-suicidal self-injury care in the perception of adolescents, young people and nurses: a systematic review of qualitative studies
Keywords: Adolescente; Adulto jovem; Comportamento autodestrutivo; Cuidados de enfermagem; Revisão; Pesquisa qualitativa; Adolescent; Young people; Self-injurious behavior; Nursing care; Review; Qualitative research; CIENCIAS DA SAUDE::ENFERMAGEM